MODEL PEMBELAJARAN KOOPERATIF NHT MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PASSING BOLA BASKET - Eka Yuda Sanjaya, I Putu (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2013)
ABSTRAK: Penelitian ini bertujuan untuk meningkatkan motivasi dan hasil belajar teknik dasar passing bola basket melalui penerapan model pembelajaran kooperatif tipe NHT pada siswa kelas X.5 SMA Negeri 1 Negara tahun pelajaran 2012/2013.Penelitian ini adalah penelitian tindakan kelas yang dilaksanakan dalam dua siklus dan masing-masing siklus dilaksanakan dua kali pertemuan. Subjek penelitian adalah siswa kelas X5 SMA Negeri 1 Negara, berjumlah 34 orang dengan rincian 21 orang putri dan 13 orang putra. Data dianalisis menggunakan analisis statistik deskriptif. Hasil analisis data pada siklus I motivasi belajar teknik dasar passing bola basket secara klasikal sebesar 11,78 (tinggi), dan pada siklus II sebesar 15,31 (sangat tinggi). Dari siklus I ke siklus II mengalami peningkatan sebesar 3,53. Persentase hasil belajar teknik dasar passing bolabasket secara klasikal pada siklus I sebesar 73,53% (cukup baik), dan pada siklus II sebesar 91.18% (sangat baik). Dari siklus I ke siklus II mengalami peningkatan sebesar 17,65%. Berdasarkan hasil analisis data dan pembahasan disimpulkan bahwa motivasi dan hasil belajar teknik dasar passing bolabasket meningkat melalui penerapan model pembelajaran kooperatif tipe NHT pada siswa kelas X5 SMA Negeri 1 Negara tahun pelajaran 2012/2013. Disarankan kepada guru Penjasorkes dapat menerapkan model pembelajaran kooperatif tipe NHT dalam proses pembelajaran Penjasorkes. Abstract: This study aims at improving the students’ motivation and learning outcome in learning Basketball basic passing technique through the implementation of Cooperative Learning type NHT for the students of Class X.5 in SMA Negeri 1 Negara in academic year 2012/ 2013. This study is a classroom action research that was carried out in two cycles. Each cycle consisted of two meetings. The subjects of this research were 34 students of Class X.5 in SMA Negeri 1 Negara, which consisted of 21 females and 13 males. The data were analyzed by using descriptive statistic analysis. The result of the data analysis of students’ motivation in learning Basketball basic passing technique classically in cycle I was 11.78, which was categorized as high. Meanwhile, in cycle II the result was 15.31, which was categorized as very high. From those results, it can be stated that the result of the students’ motivation in learning Basketball basic passing technique increased 3.53 in cycle II. The percentage of the students’ learning outcome in learning Basketball basic passing technique classically in cycle I was 73.53%, which was categorized as adequately good. In cycle II, the percentage of students’ learning outcome was 91.18%, which was categorized as very good. Thus, it can be stated that the percentage of the students’ learning outcome increased 17.65% in cycle II. From the data analysis and discussion, it can be concluded that the implementation of Cooperative Learning type NHT improved the motivation and learning outcome in learning Basketball basic passing technique of the students’ of class X.5 in SMA Negeri 1 Negara in academic year 2012/ 2013. It is suggested for the teacher of physical exercise to implement the Cooperative Learning type NHT as their method of instruction.   Kata-kata kunci: Model pembelajaran kooperatif NHT, motivasi dan hasil belajar, passing bola basket.